2020
DOI: 10.1101/2020.09.04.20188268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The link between vitamin D deficiency and Covid-19 in a large population

Abstract: BACKGROUND Recent studies suggest a link between vitamin D deficiency and Covid-19 infection. In our population we observe major differences in Covid-19 incidence in ethnic groups and genders in each group. METHODS We carried out a population-based study among 4.6 million members of Clalit Health Services (CHS). We collected results from vitamin D tests performed between 2010 and 2019 and used weighted linear regression to assess the relationship between prevalence of vitamin D deficiency and Covid-19 incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 21 publications
1
27
0
10
Order By: Relevance
“…A population-based study among 4.6 million members of a Health Services provider in Israel showed that vitamin D levels estimated between 2010 and 2019 correlated strongly with COVID-19 incidence [ 60 ]. They found that vitamin D deficiency (less than 50 nmol l −1 ), and particularly severe vitamin D deficiency (less than 30 nmol l −1 ) was much more prevalent among Ultra-orthodox and Arabs.…”
Section: Preliminary Evidence Of Associations Between Vitamin D Statumentioning
confidence: 99%
“…A population-based study among 4.6 million members of a Health Services provider in Israel showed that vitamin D levels estimated between 2010 and 2019 correlated strongly with COVID-19 incidence [ 60 ]. They found that vitamin D deficiency (less than 50 nmol l −1 ), and particularly severe vitamin D deficiency (less than 30 nmol l −1 ) was much more prevalent among Ultra-orthodox and Arabs.…”
Section: Preliminary Evidence Of Associations Between Vitamin D Statumentioning
confidence: 99%
“…Israel et al performed a large multiethnic population-based study and found a highly significant correlation between prevalence of vitamin D deficiency and incidence of confirmed SARS-CoV-2 infections [7]. Influence of vitamin D status on COVID-19-related hospital admissions, ICU admissions and mortality were not assessed in this study [7].…”
Section: Observational Studiesmentioning
confidence: 70%
“…Data from observational and intervention studies on the effect of vitamin D status and vitamin D administration during COVID-19 are conflicting. In general, larger studies of higher quality demonstrate effects on disease susceptibility [7] but not on severity or disease outcome [3,9]. Vitamin D supplementation is generally considered to be safe [22], however, this may not always be the case [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations